Toward Quantification of Agitation in People With Dementia Using Multimodal Sensing. Issue 7 (15th October 2022) - Davidoff, Hannah; Van den Bulcke, Laura; Vandenbulcke, Mathieu; De Vos, Maarten; Van den Stock, Jan; Van Helleputte, Nick; Van Hoof, Chris; Van Den Bossche, Maarten J A
Abstract: Background and Objectives: Agitation, a critical behavioral and psychological symptom in dementia, has a profound impact on a patients' quality of life as well as their caregivers'. Autonomous and objective characterization of agitation with multimodal systems has the potential to capture key patient responses or agitation triggers. Research Design and Methods: In this article, we describe our multimodal system design that encompasses contextual parameters, physiological parameters, and psychological parameters. This design is the first to include all three of these facets in an n > 1 study. Using a combination of fixed and wearable sensors and a custom-made app for psychological annotation, we aim to identify physiological markers and contextual triggers of agitation. Results: A discussion of both the clinical as well as the technical implementation of the to-date data collection protocol is presented, as well as initial insights into pilot study data collection. Discussion and Implications: The ongoing data collection moves us toward improved agitation quantification and subsequent prediction, eventually enabling just-in-time intervention.